Factors influencing work engagement among cancer survivors in Malaysia - Musa, Siti Nur Syuhada; Hamzah, Siti Raba’ah; Asimiran, Soaib; Muda, Zulaiha (Global Academic Excellence, 2021)
This study investigated the antecedents of work engagement of Malaysian employees who were cancer survivors. Work engagement refers to a positive, fulfilling, work-related state of mind characterizing employees who work hard and persist despite difficulties. Employees with high levels of work engagement are deeply involved in what they do and are happily absorbed in their work. This study was aimed to examine the individual and work environment-related factors that influence work engagement. A quantitative research paradigm was adopted, with a cross-sectional design using data collected from cancer survivors registered at the Hospital Kuala Lumpur. The 270 participants in this study were randomly selected by inclusive criteria sampling. A validated instrument was tested in a pilot study. Partial Least Square-Structural Equation Model (PLS-SEM) was used to test the direct effects of work engagement. It was found that the level of all the tested variables (work engagement, employee resilience, social support, and quality of working life) among the participants were high. This study highlights the importance of resilience and social support in improving work engagement among cancer survivors in Malaysia.